2021
DOI: 10.13107/jocr.2021.v11.i01.1948
|View full text |Cite
|
Sign up to set email alerts
|

Late Presenting Pediatric Radial Neck Fracture: A Case Report and Review of the Literature

Abstract: Introduction: A pediatric radial neck fracture, when the diagnosis is delayed, is still a challenging problem for the treating orthopedic surgeon. We report a pediatric patient with late presenting radial neck fracture and results of open reduction and fixation with Kirschner wires. Case Report: A 13-year-old right-handed girl fell on an out-stretched right arm after being tackled during playing basketball and had a radial neck fracture. However, the diagnosis of her fracture was delayed for 3 weeks. At the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Gutierrez-De La Iglesia et al studied 51 patients with Judet Types 3 and 4 fractures and concluded that there were no significant differences in functional outcome and complications between closed and open reduction [ 10 ]. Turan et al reported a case of radial neck fracture 3 weeks old managed with open reduction and internal fixation with K-wires and had good functional and radiological outcome [ 11 ]. Fracture displacement is the independent predictor of functional outcome irrespective of the technique of reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Gutierrez-De La Iglesia et al studied 51 patients with Judet Types 3 and 4 fractures and concluded that there were no significant differences in functional outcome and complications between closed and open reduction [ 10 ]. Turan et al reported a case of radial neck fracture 3 weeks old managed with open reduction and internal fixation with K-wires and had good functional and radiological outcome [ 11 ]. Fracture displacement is the independent predictor of functional outcome irrespective of the technique of reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Radial neck fractures account for 5%–10% of elbow fractures in children and usually occur between 8 and 11 years of age ( 1 ). The treatment of radial neck fractures in children is challenging, and misdiagnosis or delayed treatment may result in malunion or non-union of the radial neck, resulting in limited elbow movement ( 2 ). Judet classification is a commonly used clinical classification method for children with radial neck fractures ( 3 ), which is divided into five types according to the Angle between the vertical line at both ends of the radial head fracture and the longitudinal axis of the radial axis.…”
Section: Introductionmentioning
confidence: 99%